Penurunan Angka Kelahiran Dan Krisis Murid Baru: Tantangan Keberlangsungan Satuan Pendidikan Di Indonesia - Indrian Saputra; Renggo Pratama (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
Indonesia's demographic shift, characterized by a declining birth rate, is presenting new challenges for the sustainability of educational institutions, particularly regarding the availability of prospective new students. This study aims to analyze the implications of the declining birth rate on changes in the school-age population, the phenomenon of schools with low student enrollment, and the challenges facing the sustainability of educational institutions in Indonesia. The study employs a qualitative approach using a literature review method. Data were obtained from Statistics Indonesia (BPS) publications, policy documents from the Ministry of Basic and Secondary Education, and relevant scholarly journal articles. A descriptive-analytical approach was used, involving data reduction, data presentation, interpretation, and source triangulation. The results indicate that Indonesia's Total Fertility Rate (TFR) declined from 2.18 (based on the 2020 Population Census Long Form) to 2.13 (based on SUPAS 2025). This trend has the potential to impact the size of the school-age population in the medium to long term. However, the phenomenon of schools with low enrollment is not solely caused by the declining birth rate; it is also influenced by population mobility, residential development, public school preferences, and geographical conditions. Low student numbers affect teacher utilization, class organization, infrastructure, and financing. The study concludes that there is a need for educational planning based on school-age population projections and policies that are adaptive to demographic changes.